2019
DOI: 10.1111/anae.14681
|View full text |Cite
|
Sign up to set email alerts
|

Stress, burnout, depression and work satisfaction among UK anaesthetic trainees; a quantitative analysis of the Satisfaction and Wellbeing in Anaesthetic Training study

Abstract: Summary There is growing evidence that anaesthetic trainees experience, and may be particularly susceptible to, high levels of work stress, burnout and depression. This is concern for the safety and wellbeing of these doctors and for the patients they treat. To date, there has been no in‐depth evaluation of these issues among UK anaesthetic trainees to examine which groups may be most affected, and to identify the professional and personal factors with which they are associated. We conducted an anonymous elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 35 publications
(58 reference statements)
2
65
0
2
Order By: Relevance
“…A majority of these doctors (54%) reported excessive workloads, and a similar number believed that their workload could result in adverse events and compromise patient safety . Similarly, in the UK a 2018 survey found that, as a result of workforce shortages, trainee doctors have become increasingly stressed by workloads . This in turn has meant that large numbers of trainee doctors are considering leaving clinical work in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of these doctors (54%) reported excessive workloads, and a similar number believed that their workload could result in adverse events and compromise patient safety . Similarly, in the UK a 2018 survey found that, as a result of workforce shortages, trainee doctors have become increasingly stressed by workloads . This in turn has meant that large numbers of trainee doctors are considering leaving clinical work in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The current study is the second part of the Satisfaction and Wellbeing in Anaesthetic Training study (SWeAT). Part 1 surveyed anaesthetic trainees and non‐training grade junior anaesthetists in three UK postgraduate deaneries, and identified concerningly high incidence rates of perceived stress, risk of burnout and risk of depression . This part of the study aims to explore, using qualitative methods, which specific personal and professional factors are associated with the development of these issues, and which factors may be protective.…”
Section: Introductionmentioning
confidence: 99%
“…The current study is the second part of the Satisfaction and Wellbeing in Anaesthetic Training study (SWeAT). Part 1 surveyed anaesthetic trainees and non-training grade junior anaesthetists in three UK postgraduate deaneries, and identified concerningly high incidence rates of perceived stress, risk of burnout and risk of depression [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another survey by the Association of Anaesthetists and the Royal College of Surgeons produced similarly worrying results, and provided recommendations for action that included: more focus on a listening culture; improved rest facilities for doctors on‐call; and work patterns that better reflect the need for personal and professional development. This stress that trainees are under is further highlighted by quantitative and qualitative reports from a new survey published in this issue . This survey again highlighted workplace stressors that are perceived to have an impact on health and well‐being in anaesthetic trainees, and in some cases have resulted in depression and burnout.…”
Section: Fatigue and Burnoutmentioning
confidence: 93%